Dual-pathway Inhibition with Low-dose Aspirin and Rivaroxaban versus Aspirin Monotherapy in Patients with Coronary Artery Disease and Peripheral Artery Disease: Systematic Literature Review and Meta-analysis - Dirk Sibbing; Michael J Blaha; Rajinder Chawla; Augusto Lavalle-Cobo; Amit Kishore; Angel Lanas; Li Li; Francesca Santilli; Oliver Schnell; Zhongwei Shi (European Cardiology Review)
Background: Low-dose aspirin lowers cardiovascular event risk; dual-pathway inhibition (DPI) using low-dose aspirin with low-dose rivaroxaban may reduce this risk further. A systematic literature review and meta-analysis compared the efficacy, safety and net clinical benefit (NCB) of DPI with aspirin. Methods: PubMed and Embase were searched for randomised controlled trials reporting clinical efficacy, safety and NCB of DPI compared with aspirin alone in patients with coronary artery disease (CAD) and/or peripheral artery disease. Six articles representing four trials were included. Results: DPI versus aspirin alone significantly reduced major adverse cardiovascular events (HR 0.77; 95% CI [0.69–0.87]; p<0.01), increased International Society on Thrombosis and Haemostasis major bleeding events (HR 1.67; 95% CI [1.37–2.02]; p<0.01) and resulted in a significant NCB (HR 0.79; 95% CI [0.70–0.90]; p<0.01). Conclusion: These results underscore the potential benefit of DPI in patients with CAD, including those in the immediate post-acute coronary syndrome stage and with established CAD, as well as patients with peripheral artery disease.